7th International Symposium on Sensor Science 2019
DOI: 10.3390/proceedings2019015045
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Fibre-Optic Rotational Seismograph

Abstract: Construction, laboratory tests as well as the first field application of a new fibre-optic rotational seismograph is presented. The system based on fibre-optic gyroscope (FOG) with measured Angle Random Walk on range 10−8 rad/Sqrt(s) and a few rad/s maximum detectable amplitude of rotation in frequency range from DC to 328.12 Hz designed it for rotational seismology area of interest. This work presents also exemplary relevant measurements which were conducted using two seismographs in the geophysical observato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…A major advantage of fibre-optical sensors is that they are inherently insensitive to translational motion. Fibre-optic gyroscopes were already successfully employed for seismological applications [28,[123][124][125][126][127]. Recently, the first commercial fiber optic gyroscope designed specifically for the needs of seismology has become available blueSeis-3A by iXBlue, France [12].…”
Section: Direct Observationsmentioning
confidence: 99%
“…A major advantage of fibre-optical sensors is that they are inherently insensitive to translational motion. Fibre-optic gyroscopes were already successfully employed for seismological applications [28,[123][124][125][126][127]. Recently, the first commercial fiber optic gyroscope designed specifically for the needs of seismology has become available blueSeis-3A by iXBlue, France [12].…”
Section: Direct Observationsmentioning
confidence: 99%
“…Physically each sensor can be divided into two basic parts: optical and electronic. The optical part, according to the schema in Figure 2, assures the Sagnac effect reversibility [17] and is constructed according to the description presented in our previous papers [11,13,15,19]. Only a substitution of a fiber coupler in loop and a piezoceramic phase modulator by a multifunction integrated optic chip (MIOC) (Idealphotonics Ltd., Shanghai, China) have been applied.…”
Section: Construction and Laboratory Investigation Of The Fiber-opmentioning
confidence: 99%
“…For the above reasons, this extended paper relates to a manuscript presented at the 7th International Symposium on Sensor Science (I3S2019) in Naples, Italy [15], in which we described the construction and laboratory tests, as well as results of field application of the set of two identical FOSREM ® —the innovative Fiber-Optic Rotational Seismograph. During the field test conducted in the geophysical observatory in Książ, Poland, torsion and tilt effects resulting from mining seismic quakes induced by copper mining operations have been recorded by them (FOSREMs) with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, in most of the available seismic codes and numerical methods, the seismic load is defined as a clear translational ground motion, which describes the characteristic of Primary (P) and Secondary (S) body wave propagations through the ground. At the same time, the rotational load, generated mostly by Rayleigh (R) and Love (L) surface waves, as well as with body wave interactions with the ground surface [27], are neglected, mainly due to the lack of rotational measurements of the ground motion [28][29][30]. The significant development in six degrees of freedom (6-DoF) measurements of earthquakes and mining induced tremors has been noticed in the last 10 years when numerous essential research works have been reported in the field of development of new systems for integrated measurements of rotational and translational components of the ground motion [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%